2006
DOI: 10.1038/sj.pcan.4500895
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene inhibits DNA synthesis in primary prostate epithelial cells in vitro and its administration is associated with a reduced prostate-specific antigen velocity in a phase II clinical study

Abstract: Interest in lycopene has focused primarily on its use in the chemoprevention of prostate cancer (CaP); there are few clinical trials involving men with established disease. In addition, most data examining its mechanism of action have been obtained from experiments using immortal cell lines. We report the inhibitory effect(s) of lycopene in primary prostate epithelial cell (PEC) cultures, and the results of a pilot phase II clinical study investigating whole-tomato lycopene supplementation on the behavior of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 24 publications
1
33
0
1
Order By: Relevance
“…Of relevance to prostate cancer, lycopene has been shown to inhibit DNA synthesis (Barber et al, 2006). Lycopene also inhibits growth of hormone-dependent LNCaP and C4-2 prostate cancer cell lines without affecting PSA mRNA expression (Peternac et al, 2008), and increases expression of PPARgamma and LXRalpha in LNCaP cells .…”
Section: In Vitro Datamentioning
confidence: 99%
“…Of relevance to prostate cancer, lycopene has been shown to inhibit DNA synthesis (Barber et al, 2006). Lycopene also inhibits growth of hormone-dependent LNCaP and C4-2 prostate cancer cell lines without affecting PSA mRNA expression (Peternac et al, 2008), and increases expression of PPARgamma and LXRalpha in LNCaP cells .…”
Section: In Vitro Datamentioning
confidence: 99%
“…Three before-after studies reported a significant reduction in PSA after intervention, [30][31][32] whereas two did not see any change in PSA. 33,34 In the study by Kim et al, 35 32 prostate cancer patients awaiting prostatectomy and treated with lycopene supplementation (tomato sauce 30 mg per day) for 3 weeks were compared with 34 controls also undergoing prostatectomy for prostate cancer.…”
Section: Change In Psa Levelsmentioning
confidence: 99%
“…Five had no control (before-after design) [30][31][32][33][34] and one had an unmatched control group; 35 it was unclear how the control group was selected. The remaining two studies were RCTs, but one 36 was very small and included 35 patients with data available for analysis from only 26 patients.…”
Section: Lycopene Supplementation and Prostate Cancer Progression F Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term lycopene supplementation in men with localized prostate cancer was shown to lower serum prostate-specific antigen (PSA) levels (as a measure of prostate cancer progression) over 3 weeks to 1 year, though only two of four studies were placebo-controlled. 15,[22][23][24] In the only epidemiologic study to date, in 1,202 men in the Health Professionals Follow-up Study with localized/regional prostate cancer, being in the highest quartile of postdiagnosis tomato sauce intake, compared to being in the lowest quartile, was associated with lower risk of prostate cancer progression (defined as PSA recurrence, metastasis or prostate cancer death) [hazard ratio (HR) 5 0.56, 95% confidence interval (CI) 0.38-0.82]. 6 No previous study has examined the association of dietary lycopene intake or tomato products with prostate cancer-specific mortality (PCSM).…”
mentioning
confidence: 99%